OPTIMALISASI KINERJA SANITARIAN DENGAN PEDEKATAN ANALISIS KOMPREHENSIF FAKTOR INTERNAL DAN EKSTERNAL DI PUSKESMAS SE-BANDUNG RAYA - Teguh Budi Prijanto; Azhar Affandi; Heru Setiawan (Poltekkes Kemenkes Bandung, 2025)
Sanitarian performance can be influenced by various factors, both internal and external. Understanding the influence of these factors is important to increase the commitment and effectiveness of sanitarian work. This research aimed to determine the influence of the work environment, work discipline, workload, and work motivation on sanitarian work commitment and its implications for sanitarian performance. The method used descriptive and verificative quantitative approach. The sample includes all Sanitarian in Community Health Centers throughout Bandung Raya totaling 222 people. Data were analyzed using Structural Equation Modeling (SEM) Techniques. The descriptive analysis showed influence of work environment, work discipline, workload, and work motivation on sanitarian work commitment are in category of being quite good towards good. The research verifiably showed influence work environment, work discipline, workload,and work motivation on sanitarian work commitment at Community Health Centers throughout Bandung Raya by 75.3%. Work commitment has a significant influence of 82.8% on sanitarian performance in environmental health services. The remaining 17.2% of sanitarian performance was influenced by other factors not studied in this study. This research confirms that sanitarian work commitment has a positive effect on their performance in health services. By understanding the factors that influence commitment and performance. Health center management can take strategic steps to create a more supportive work environment, improve discipline, manage workload, and motivate sanitarians. It is hoped this will improve the quality of environmental health services provided to the community, as well as create sanitarians who are more committed and productive in carrying out their duties.